Mineral lick monitoring reveals seasonal patterns of bot fly myiasis in howler monkeys (Alouatta sara) - Sam Pottie; Gladys Tapara; Adrian Forsyth (European Journal of Wildlife Research, 2026)

Sequence analysis of a viral strain isolated for the first time in the UK, clarifies the identity of a novel species of fabavirus - Naomi Beddoe; Sam McGreig; Adrian Fox; Ian P. Adams; Alec Forsyth (Archives of Virology, 2026)
For the first time sequence data of a fabavirus was identified in dahlia from the UK, which was similar to virus sequence reported from dahlia in China. Initial sequences were determined by high-throughput sequencing (HTS) using the Illumina MiSeq platform, and were verified by Sanger sequencing and 5’ and 3’ rapid amplification of cDNA ends (RACE) polymerase chain reaction (PCR). The genome comprised two RNAs that were 5,851 nucleotide (nt) and 3,468 nt long, excluding the 3’-end poly-A tails, each RNA coded for a single polyprotein. The amino acid (aa) sequence identity percentages shared with recognised Fabavirus members over the protease-polymerase (Pro-Pol), Large Coat Protein (LCP) and combined Coat protein (CP) regions were in range with current demarcation thresholds for a distinct Secoviridae species. These sequence data analyses indicate that the fabavirus sequences identified in dahlia in both China and the UK represent a novel species in the family Secoviridae , genus Fabavirus . The name dahlia fabavirus (DFV) is proposed for this putative novel species tentatively named “ Fabavirus dahliae ”.

Rare Amazonian canids revealed: record camera trap detections of the short-eared dog (Atelocynus microtis) and bush dog (Speothos venaticus) in southeastern Peru - Sam Pottie; Erin Marcela Rivera Groves; Flor Maria Perez Mullisaca; Caleb Jonatan Quispe Quispe; Rosio Vega Quispe; Christopher Beirne; Andrew Whitworth; Adrian Forsyth (Mammal Research, 2026)

An unusual association: co-use of mineral licks by howler and spider monkeys (Alouatta sara and Ateles chamek) - Sam Pottie; Gladys Tapara; Adrian Forsyth (Primates, 2026)

Nerine potexvirus 1: a new Potexvirus species detected from Nerine in the United Kingdom - Naomi Beddoe; Sam McGreig; John Walsh; Adrian Fox; Ian P. Adams; Alec Forsyth (Journal of Plant Pathology, 2023)

Disappearance of an ecosystem engineer, the white-lipped peccary (Tayassu pecari), leads to density compensation and ecological release - Andrew Whitworth; Christopher Beirne; Arianna Basto; Eleanor Flatt; Mathias Tobler; George Powell; John Terborgh; Adrian Forsyth (Oecologia, 2022)
Given the rate of biodiversity loss, there is an urgent need to understand community-level responses to extirpation events, with two prevailing hypotheses. On one hand, the loss of an apex predator leads to an increase in primary prey species, triggering a trophic cascade of other changes within the community, while density compensation and ecological release can occur because of reduced competition for resources and absence of direct aggression. White-lipped peccary ( Tayassu pecari —WLP), a species that typically co-occurs with collared peccary ( Pecari tajacu ), undergo major population crashes—often taking 20 to 30-years for populations to recover. Using a temporally replicated camera trapping dataset, in both a pre- and post- WLP crash, we explore how WLP disappearance alters the structure of a Neotropical vertebrate community with findings indicative of density compensation. White-lipped peccary were the most frequently detected terrestrial mammal in the 2006–2007 pre-population crash period but were undetected during the 2019 post-crash survey. Panthera onca (jaguar) camera trap encounter rates declined by 63% following the WLP crash, while collared peccary, puma ( Puma concolor ), red-brocket deer ( Mazama americana ) and short-eared dog ( Atelocynus microtis ) all displayed greater encounter rates (490%, 150%, 280%, and 500% respectively), and increased in rank-abundance. Absence of WLP was correlated with ecological release changes in habitat-use for six species, with the greatest increase in use in the preferred floodplain habitat of the WLP. Surprisingly, community-weighted mean trait distributions (body size, feeding guild and nocturnality) did not change, suggesting functional redundancy in diverse tropical mammal assemblages.

Understanding Trait‐Dependent Community Disassembly: Dung Beetles, Density Functions, and Forest Fragmentation - TROND H. LARSEN; ALEJANDRO LOPERA; ADRIAN FORSYTH (Conservation Biology, 2008)
Anthropogenic disturbances such as fragmentation are rapidly altering biodiversity, yet a lack of attention to species traits and abundance patterns has made the results of most studies difficult to generalize. We determined traits of extinction‐prone species and present a novel strategy for classifying species according to their population‐level response to a gradient of disturbance intensity. We examined the effects of forest fragmentation on dung beetle communities in an archipelago of 33 islands recently created by flooding in Venezuela. Species richness, density, and biomass all declined sharply with decreasing island area and increasing island isolation. Species richness was highly nested, indicating that local extinctions occurred nonrandomly. The most sensitive dung beetle species appeared to require at least 85 ha of forest, more than many large vertebrates. Extinction‐prone species were either large‐bodied, forest specialists, or uncommon. These explanatory variables were unrelated, suggesting at least 3 underlying causes of extirpation. Large species showed high wing loading (body mass/wing area) and a distinct flight strategy that may increase their area requirements. Although forest specificity made most species sensitive to fragmentation, a few persistent habitat generalists dispersed across the matrix. Density functions classified species into 4 response groups on the basis of their change in density with decreasing species richness. Sensitive and persistent species both declined with increasing fragmentation intensity, but persistent species occurred on more islands, which may be due to their higher baseline densities. Compensatory species increased in abundance following the initial loss of sensitive species, but rapidly declined with increasing fragmentation. Supertramp species (widespread habitat generalists) may be poor competitors but strong dispersers; their abundance peaked following the decline of the other 3 groups. Nevertheless, even the least sensitive species were extirpated or rare on the smallest and most isolated islands.

Female mimicry and resource defense polygyny by males of a tropical rove beetle, Leistotrophus versicolor (Coleoptera : Staphylinidae) - Adrian Forsyth; John Alcock (Behavioral Ecology and Sociobiology, 1990)

Post-copulatory aggression toward their mates by males of the rove beetle Leistotrophus versicolor (Coleoptera: Staphylinidae) - John Alcock; Adrian Forsyth (Behavioral Ecology and Sociobiology, 1988)

Alternative reproductive tactics in the territorial damselflyCalopteryx maculata: sneaking by older males - Adrian Forsyth; Robert D. Montgomerie (Behavioral Ecology and Sociobiology, 1987)

Alternative reproductive tactics in the territorial damselflyCalopteryx maculata: sneaking by older males - Adrian Forsyth; Robert D. Montgomerie (Behavioral Ecology and Sociobiology, 1987)